The neuronal identity of triple negative breast cancer - Le, Thanh. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Madeleine Oudin.; Committee: David Kaplan, Brent Cochran, Abigail Koppes, and Frank Gertler.; Keywords: Biomedical engineering, and Canadian history.